2023
DOI: 10.1038/s41598-023-39215-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of metabolic pathways contributing to ER+ breast cancer disparities using a machine-learning pipeline

Abstract: African American (AA) women in the United States have a 40% higher breast cancer mortality rate than Non-Hispanic White (NHW) women. The survival disparity is particularly striking among (estrogen receptor positive) ER+ breast cancer cases. The purpose of this study is to examine whether there are racial differences in metabolic pathways typically activated in patients with ER+ breast cancer. We collected pretreatment plasma from AA and NHW ER+ breast cancer cases (AA n = 48, NHW n = 54) and cancer-free contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…The metabolic pathway involving glycine, serine, and threonine has been associated with breast cancer invasion [34] and may serve as a predictor for the response to neoadjuvant chemotherapy, particularly in triple-negative breast cancer [25]. Furthermore, serum threonine levels have shown signi cant variance in relation to responses to neoadjuvant chemotherapy in breast cancer patients [33], and plasma methionine levels were reported to be lower in ER-positive breast cancer patients compared to a healthy control group [35]. Hydroxyproline, a non-essential amino acid integral to collagen, has been noted for its altered levels in colorectal cancer [36].…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic pathway involving glycine, serine, and threonine has been associated with breast cancer invasion [34] and may serve as a predictor for the response to neoadjuvant chemotherapy, particularly in triple-negative breast cancer [25]. Furthermore, serum threonine levels have shown signi cant variance in relation to responses to neoadjuvant chemotherapy in breast cancer patients [33], and plasma methionine levels were reported to be lower in ER-positive breast cancer patients compared to a healthy control group [35]. Hydroxyproline, a non-essential amino acid integral to collagen, has been noted for its altered levels in colorectal cancer [36].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, African American (AA)/Black individuals are known to possess a significantly greater cancer burden, with the poorest likelihood of survival leading to the worst incidence of death of any race with regard to various types of cancer [34]. Consequently, AA women (AAW)/Black women have a 41% higher mortality rate compared to White women/non-Hispanic White (NHW) women [34,35]. For BC, racial disparities are accentuated in Black women, who have a lower incidence than White and Asian women, while their BC-related mortality and aggressiveness are the highest among all races [36].…”
Section: Race-and Ethnicity-based Disparities In Breast Cancermentioning
confidence: 99%
“…Furthermore, even if the known risk variables do not entirely account for racial/ethnic variations in risk, the same authors demonstrated that relationships between obesity and oral contraceptive (OC) use with ER+ and ER− BCR differ by race/ethnicity [58]. The disparities are also particularly pronounced in ER+ BC patients, with AAW with ER+ subtype of BC experiencing four-five times higher mortality rates than their white counterparts [35].…”
Section: Breast Cancer Disparities Are Associated With Tumor Biologymentioning
confidence: 99%
“…Santaliz Casiano et al found that amino acid levels are significantly lower in AA breast cancer patients than in healthy individuals [ 59 ]. The pathways associated with energy metabolism are glycolysis, amino acid metabolism, and the TCA cycle, which dominate in AA women with ER+ tumors, potentially indicating the aggressiveness of their tumors [ 76 ].…”
Section: Diagnostic Value Of Determination Of Amino Acids In Biologic...mentioning
confidence: 99%